(untitled) (Al-Qamar, 2018)
History of the compilation of the Quran has frequently been discussed by the orientalists. Ibn warrāq in “The Origins of the Quran: Classic Essays on Islam’s Holy Book” has compiled the works of different orientalists from the referred perspective. This paper studies the arguments developed by the orientalists in the mentioned book on the early history of compilation of the Quran. It finds that these works, negating the thoroughness concerning compilation of the Quran, put a question mark on its authenticity. This study rejects the orientalist’s assertions and supports the Muslim claim of accuracy observed during the compilation of the Quran with historical evidences and logical arguments.